Robust ferromagnetism in wafer-scale Fe3GaTe2 above room-temperature - Shuxiang Wu; Zhihao He; Minghui Gu; Lizhu Ren; Jibin Li; Bo Deng; Di Wang; Xinhao Guo; Wanjiong Li; Mingyi Chen; Yijun Chen; Meng Meng; et al. (Nature Communications)
Abstract The discovery of ferromagnetism in van der Waals (vdW) materials has enriched the understanding of two-dimensional (2D) magnetic orders and opened new avenues for fundamental physics research and next generation spintronics. However, achieving ferromagnetic order at room temperature, along with strong perpendicular magnetic anisotropy, remains a significant challenge. In this work, we report wafer-scale growth of vdW ferromagnet Fe3GaTe2 using molecular beam epitaxy. The epitaxial Fe3GaTe2 films exhibit robust ferromagnetism, exemplified by high Curie temperature (T C  = 420 K) and large perpendicular magnetic anisotropy (PMA) constant K U = 6.7 × 105 J/m3 at 300 K for nine-unit-cell film. Notably, the ferromagnetic order is preserved even in the one-unit-cell film with T C reaching 345 K, benefiting from the strong PMA (K U = 1.8×105 J/m3 at 300 K). In comparison to exfoliated Fe3GaTe2 flakes, our epitaxial films with the same thickness show the significant enhancement of T C, which could be ascribed to the tensile strain effect from the substrate. The successful realization of wafer-scale ferromagnetic Fe3GaTe2 films with T C far above room temperature represents a substantial advancement (in some aspects or some fields, e.g. material science), paving the way for the development of 2D magnet-based spintronic devices.